Attractant and phagostimulant effects of aqueous extract of cassava, Manihot esculenta, tuber on Coptotermes curvignathus and Coptotermes gestroi (Isoptera: Rhinotermitidae) - Castill, Venite; Sajap, Ahmad Said; Sahri, Mohd Hamami (Sociobiology, 2010)
Effects of aqueous extracts of cassava tuber, Manihot esculenta, were evaluated on subterranean termites, Coptotermes curvignathus and Coptotermes gestroi (Isoptera: Rhinotermitidae). The termites were exposed to filter papers that had been treated with various concentrations of aqueous extract of cassava, and their responses to the treated papers in terms of their consumption, survival and attractiveness were compared with those of untreated papers. The results show that C. curvignathus and C. gestroi significantly preferred papers that had been treated with 10% and 5% of cassava tuber extract, respectively. Both termite species were significantly attracted to and consumed more treated papers than the untreated papers. Survival rates in treated groups were slightly lower than those in the control, but they were not significantly different. However, the termites survived poorly on papers that had been treated with cassava tuber extract higher than 15% concentration. This could be due to intoxication caused by cynogenic glycosides present in the cassava.